Prevalence and characteristics of peptic ulcer in patients presenting with hematemesis and/or melena undergoing esophagogastroduodenoscopy: a descriptive study - Hidayanto, Arif; Subrata, Sumarno Adi; Widiyanto, Puguh (Universitas Muhammadiyah Magelang, 2025)
Peptic ulcers are a leading cause of upper gastrointestinal bleeding, with the highest incidence observed among men and the elderly. Esophagogastroduodenoscopy (EGD) is the gold standard diagnostic tool, offering sensitivity and specificity rates of up to 90% for identifying peptic ulcers. This study aimed to describe the characteristics of peptic ulcer cases in patients presenting with hematemesis and/or melena who underwent EGD at RSUD Temanggung in 2023. A quantitative descriptive design was utilized, employing retrospective data collection from medical records of patients who met the inclusion and exclusion criteria. A total of 23 medical records were analyzed. Among the 23 cases of hematemesis and/or melena, peptic ulcers were the most common diagnosis, accounting for 47.8% (11 cases). Erosive gastritis was the second most common diagnosis (39.1%, 9 cases), followed by esophageal varices (13.0%, 3 cases). Of the 11 patients diagnosed with peptic ulcers, 63.6% were aged over 60 years, 27.3% were aged 40–59 years, and 9.1% were aged 19–39 years. Regarding gender, 81.8% of peptic ulcer patients were male, and 18.2% were female. The majority (90.9%) of patients had ulcers classified as Forrest III, while 9.1% were classified as Forrest IIc. The most common nursing problems identified included ineffective tissue perfusion (36.4%), nausea (36.4%), and pain (27.2%). The findings highlight that the majority of peptic ulcer cases involved Forrest III ulcers, and key nursing concerns included managing ineffective peripheral tissue perfusion and nausea. This study underscores the need for targeted interventions to address these common nursing problems and improve patient outcomes in peptic ulcer management. Keywords: Endoscopy, esophagogastroduodenoscopy, hematemesis, melena, peptic ulcer